Synthetic hydroxyapatite obtaining using three different methods and characterization to use it as bone substitute (2012)
The method by which to obtain Hydroxyapatite to be used as bone substitute should offer specific qualities such as, high purity, performance, low cost and has to be the following, bioactive, biocompatible, it has to have osteoconductivity and it has to bond directly to the bone. In this paper, synthetic HAp was prepared using 3 different methods reported in the literature as a route via sintering and precipitation, and subsequently characterized by atomic absorption spectrometry (AAS), molecular absorption spectrometry (UV-Vis), infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy X-ray (EDX). The route of synthesis of HAp precipitation gives better results, compared to the commercial standard sample and bovine bone, such as grain size which is of about 1 µm, molar ratio Ca/P of 1.7, high purity and crystallinity, while the results obtained via sintering show the presence of amorphous phases. The synthesis method using a wet precipitation of calcium nitrates and phosphates is practical and suitable for the immobilization of HAp on a metal substrate such as silicon, important for the use in dental and medical reconstructive surgery.